THE EFFECT OF COMPANY IMAGE AND SERVICE QUALITY ON THE SATISFACTION OF LION AIR USERS IN WEST JAVA - Hasanawi, Hasanawi; Farhan, Farhan (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The airlines industry encompasses various companies that provide flight services for passengers and cargo, and involves various aspects of complex management. In Indonesia, the airline industry continues to grow and develop in line with economic development and increased community mobility. This has created intense competition among airlines that are competing to offer better service and satisfaction. One of the long-standing players in the Indonesian airline industry is Lion Air. The purpose of this study was to determine the effect of Company Image and Service Quality on User Satisfaction of Lion Air airlines in West Java. The type of research used is descriptive and verification with an approach using quantitative methods, The results of data research, then the research instrument analysis, classical assumption test, descriptive and verification analysis. The results of the study show that most respondents gave high ratings to the variables of Company Image, Service Quality, and User Satisfaction of Lion Air airlines in West Java. Company Image and Service Quality have a positive and significant influence on User Satisfaction, both partially and simultaneously. The contribution of these two variables is